A novel method to grow silicon nitride whiskers during sintering - Kim, S.; Kim, C. (Materials Science and Technology, 2005)
In this study a novel method to grow silicon nitride whiskers at the inside of large pores formed intentionally during liquid sintering was developed. Sintering was done at 1850°C with silicon nitride powders and sintering additives such as alumina and yttria under nitrogen atmosphere. As experimental variables, pore size, volume % of pore, and nitrogen pressure were used. Silicon nitride whiskers were well grown at low volume % of pores such as 14% and 27% but not grown at high volume % of pores such as 39% and 50%. On the other hand, the variation of pore size and nitrogen pressure did not have any influence on the whisker growth. In conclusion, the most significant factor to grow silicon nitride whiskers at the inside of large pores during sintering was to maintain low volume % of pores, that is, closed pores.